Studying Mustahik Requirements Based on Had Kifayah Benchmark: A Case from East Nusa Tenggara (NTT) - Kamilah Kinanti (Center of Strategic Studies (PUSKAS) BAZNAS, 2019)
As an effort to optimize the transparent and measurable zakat management, BAZNAS Center of Strategic Studies has been developing several instruments, including the Had Kifayah measure. The measurement is the standard limit of basic needs of a Muslim, which is helpful to consider the requirements of zakat recipients. By employing Had Kifayah, this paper performs a case study from Nusa Tenggara Timur (NTT) Province in 2018 and finds that NTT had the highest cost of living of IDR3,363,105.00 per family (monthly). This paper covers the preliminary study verifying the categorization pyramid as in Had Kifayah standard to investigate the changes of a mustahik income and expenditure before and after the productive zakat program of BAZNAS. The results show that the program conducted by BAZNAS-NTT from 2016 to 2017 is found to be in the fourth priority on the Had Kifayah pyramid. Keyword: Had Kifayah, priority pyramid of Had Kifayah, Mustahik of Productive Zakat Program, Nusa Tenggara Timur (NTT)